Human rights, disability and social inclusion - Vega Espejo, Guillermo César (2019)
This document presents an analysis of disability and social inclusion as a human rights issue; we describe the three models that have been established to understand historical evolution in how to address the issue and how along the way a series has been defeated of paradigms and prejudices that contrasted with the social reality of people with disabilities in terms of their value as people with potentialities and talents who were not harnessed or were invisible. A reflection is made of the contemporary situation of people with disabilities, especially touching children and the difficulties they still encounter today, as well as the great challenge of the States to design policies, programs and projects capable of defeating the mistreatment still in force and for systems to be built in which equal opportunities prevail.